2022
DOI: 10.3389/fmicb.2022.785502
|View full text |Cite
|
Sign up to set email alerts
|

How Ciliated Protists Survive by Cysts: Some Key Points During Encystment and Excystment

Abstract: Forming cysts is a common and important bionomic strategy for microorganisms to persist in harsh environments. In ciliated protists, many species have been reported to form cysts when facing unfavorable conditions. Despite traditional studies on the morphological features of cysts and the chemical composition of cyst wall, recent research has focused more on the molecular mechanisms of encystment. The present work reviews studies on developmental features and molecular information of resting cysts in ciliates,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 111 publications
(215 reference statements)
0
13
0
Order By: Relevance
“…2003; Javaux & Lepot 2017; Agić & Cohen 2021) given that they require not only elaborate morphostructure but also tightly controlled enzymatic activity to release the operculum while leaving the rest of the vesicle unaffected (Chambers & Thompson 1972; Li et al . 2022). Operculate structures are not known from prokaryotes, but do occur broadly across modern protistan groups (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…2003; Javaux & Lepot 2017; Agić & Cohen 2021) given that they require not only elaborate morphostructure but also tightly controlled enzymatic activity to release the operculum while leaving the rest of the vesicle unaffected (Chambers & Thompson 1972; Li et al . 2022). Operculate structures are not known from prokaryotes, but do occur broadly across modern protistan groups (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…The previous study showed that autophagic vacuoles in stage C might digest the organelles and other structures for supplying energy and materials for biosynthetic to maintain life activities and provide the condition for cyst (Li et al, 2022). Our study revealed oxidative phosphorylation and starch and sucrose metabolism were significantly enriched in stage C compared to stage G of A .…”
Section: Discussionmentioning
confidence: 99%
“…In recent decades, research studies on ciliate cysts mainly focused on physiological diversity and morphological structure by ultrastructural analysis (Gutiérrez et al, 2001; Kida & Matsuoka, 2006; Verni & Rosati, 2011). It was reported that the process of encystment including structural changes and the morphology of cysts varied among ciliate species (Corliss & Esser, 1974; Li et al, 2022; Van Wagtendonk, 1955). A few studies have suggested that ciliate cyst formation was a complex process regulated jointly by signaling pathways and reported some genes related to this process, including ubiquitin, Ca 2+ ‐ATPase, actin, and MAPK‐related kinase (Gao et al, 2015; Grisvard et al, 2008; Jiang et al, 2019; Pan et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Encysting species can sustain relatively high mortality rates because those refer to trophonts (i.e., motile cells) only (Weisse et al 2023b). Encysted specimens may survive starvation and other unfavorable conditions for a long time (Verni and Rosati 2011;Li et al 2022). Therefore, relatively high mortality rates of the trophonts of cyst-forming ciliates may reduce the species' fitness only moderately.…”
Section: Physiological Mortality Vs Predator-induced Mortalitymentioning
confidence: 99%